2021
DOI: 10.1097/qmh.0000000000000343
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Preanalytical Errors Using Quality Indicators in a Hematology Laboratory

Abstract: Background and Objectives: Monitoring laboratory performance continuously is crucial for recognizing errors and fostering further improvements in laboratory medicine. This study aimed to review the quality indicators (QIs) and describe the laboratory errors in the preanalytical phase of hematology testing in a clinical laboratory. Methods: All samples received in the Hematology Laboratory of the Maternity and Pediatric Hospital in Hail for 3 years were retrospectively revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
0
0
1
Order By: Relevance
“…21 Studies have been conducted that showed 2-4 times reduction in pre analytical errors when the staff was properly trained. 11,19,20 In the assessment of knowledge for microbiological investigations it was found that both doctors and nurses did not have good knowledge about the time of collection and nature of the specimen required. Higher mean value was observed in the awareness of doctors as compared to nurses.…”
Section: Discussionmentioning
confidence: 99%
“…21 Studies have been conducted that showed 2-4 times reduction in pre analytical errors when the staff was properly trained. 11,19,20 In the assessment of knowledge for microbiological investigations it was found that both doctors and nurses did not have good knowledge about the time of collection and nature of the specimen required. Higher mean value was observed in the awareness of doctors as compared to nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, more sources of preanalytical error have been studied, and various measures (Figure 3) have been taken to minimize the error. *Harmonization [10]; *Education and training [30,31]; *Hemolytic, icteric, lipemic [4,5,32]; *Quality monitoring [33][34][35]; *Automation [34,36,37] Image Credit: Susmita Sinha…”
Section: Measures To Improve Preanalytical Errorsmentioning
confidence: 99%
“…Realizing the importance of preanalytical error, many laboratories incorporate the performance of the preanalytical phase as their quality indicator (QI). Studies have proven that this exercise has significantly reduced laboratory error [34,35]. There have been efforts by the International Federation of Clinical Chemistry (IFCC) working group on laboratory errors and patient safety (WG-LEPS) to standardize the implementation of preanalytical error monitoring by developing a model of QI (MQI) [32].…”
Section: Quality Monitoringmentioning
confidence: 99%
“…Indicadores preanalíticos: tipo de muestra incorrecto, contenedor de muestra incorrecto, nivel de llenado incorrecto, muestra coagulada, muestra hemolizada, muestra no recibida Alshaghdali et al, (2022Alshaghdali et al, ( ) 2022 Laboratorio de Hematología del Hospital de Maternidad y Pediatría de Hail, Arabia Saudita / 3 años.…”
Section: Rohilla Et Al (2021) 2021unclassified